(untitled) (Third Sector Social Economic Review, 2018)
The general purpose of this study, which analyzes social enterpreneurship’s employment with the sample of Ashoka Turkey is to determine the factors that encourage individuals to work in social entrepreneurships. The sub-goals around this main objective are; determining the employment potentials of social entrepreneurships; poverty, unemployment, education, environment and social problems that are of interest to social policy. In the direction of these aims of the research using ""survey"" technique from quantitative research techniques; Ashoka members in Turkey with those employed in social entrepreneurships and social entrepreneurs manage a research model to determine the perception was assembled. According to the results of the research, it is changing the traditional understanding that entrepreneurship can only be carried out on the commercial field and working can be done only for the purpose of income and creates a new field of employment within the scope of this understanding and also has the potential to support the social expenditures of the state with the contributions made to the welfare services at the same time.